A qualitative study of the knowledge-brokering role of middle-level managers in service innovation: managing the translation gap in patient safety for older persons’ care - Currie, Graeme; Burgess, Nicola; White, Leroy; Lockett, Andy; Gladman, John R.F.; Waring, Justin (NIHR Journals Library, 2014)
Background: Brokering of evidence into service delivery is crucial for patient safety. We study knowledge brokering by ‘hybrid’ middle-level managers (H-MLMs), who hold responsibility for clinical service delivery as well as a managerial role, in the context of falls, medication management and transition, in care of older people.